INEQUALITY OF HOUSEHOLD INCOME IN INVOLUNTARY RESETTLEMENT AT KOTO PANJANG - UTRI SAFRI YETMI; FERY ANDRIANUS; ZULKIFLI N (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This research examined inequality of household income transferred due to the construction involuntary resettlement of the Koto Panjang dam in Kampar District, Riau Province. Dam construction caused the displaced of the households in the location. The households received compensation in the form of buildings and land. Even though the displaced household received the same compensation but some households had better lives while others were worse. This condition showed the inequality of household income in the new location. This study used primary data that obtained through questionnaires in 3 sub-districts of 10 villages. The analytical tool used to see the income inequality was the Gini ratio. This study found that the inequality of household income transferred in Koto Panjang was moderate. This showed that the households that have been moved due to the construction of the Koto Panjang Dam have been quite good compared to before.